An Analysis of a Conflict Between the Theories of Creationism and Science in the Experience of a Pre-service Physics Teacher - Lukie, Michael Paul (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2021)
This paper explores a conflict a pre-service physics teacher experienced while completing a teaching practicum at a religious high school that supported creationism. As a result of the conflict, the pre-service teacher was scapegoated by the staff and students at the school. An analysis of the projective dynamics involved in this conflict are explored including scapegoating, psychic inflation, fanaticism for science, and what was constellated in the pre-service teacher’s personal, familial, and cultural unconscious. In examining the pre-service teacher’s unconscious, it will be suggested that religion is part of the pre-service teacher’s repressed shadow and the cooperating/mentor teacher’s religious projections helped to constellate this shadow element. By examining the conflicts that arise between pre-service teachers and their cooperating teachers as a result of psychodynamics and differing worldviews, educators can begin to understand how analytical psychology may be applied so that such conflicts may be depotentiated in the future.